2016
DOI: 10.1002/jcsm.12160
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and physical independence in older adults: the independent and synergic role of muscle mass and muscle function

Abstract: BackgroundThe loss of skeletal muscle mass (MM) or muscle function (MF) alone increases the risk for losing physical independence in older adults. We aimed to examine the independent and synergic associations of low MM and low MF, both criteria of sarcopenia, with the risk for losing projected physical independence in later life (+90 years old).MethodsCross‐sectional analyses were conducted in 3493 non‐institutionalized older adults (1166 males). Physical independence was assessed with a 12‐item composite phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(171 citation statements)
references
References 42 publications
5
157
0
9
Order By: Relevance
“…Our results clearly show the differences between older adults with sarcopenia and non‐sarcopenia in the performance in gait speed and the level of dependence. As shown in previous studies, our findings confirm that sarcopenia results in lower gait speed and independence in daily living . Consequently, the promotion of physical activity in older adults is key to maintain the muscle mass to prevent the deterioration of gait speed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results clearly show the differences between older adults with sarcopenia and non‐sarcopenia in the performance in gait speed and the level of dependence. As shown in previous studies, our findings confirm that sarcopenia results in lower gait speed and independence in daily living . Consequently, the promotion of physical activity in older adults is key to maintain the muscle mass to prevent the deterioration of gait speed.…”
Section: Discussionsupporting
confidence: 90%
“…In Colombia, recent results from SABE Bogota study estimated that sarcopenia affects 11.5% of the older population . Sarcopenia is related to several functional comorbidities including mobility disorders, risk of falls and fractures, and a loss of physical independence in activities of daily living (ADL) . It seems that sarcopenia depends on several coadjuvant factors such as inflammatory processes related to aging, nutritional status, intramuscular fat, and genetics, in addition to the reduction of physical activity, which is a crucial precursor of sarcopenia .…”
Section: Introductionmentioning
confidence: 99%
“…36 The prevalence of sarcopenia in Asia ranges from 4.1% to 11.5% of the general older population. 38 In acute care wards, sarcopenia was an independent predictor of 3 year mortality (adjusted hazard ratio: 2.49; 95% confidential interval: 1.25-4.95) and readmission (adjusted hazard ratio: 1.81; 95% confidential interval: 1.17-2.80) after adjustment for age, sex, and other confounders. 38 In acute care wards, sarcopenia was an independent predictor of 3 year mortality (adjusted hazard ratio: 2.49; 95% confidential interval: 1.25-4.95) and readmission (adjusted hazard ratio: 1.81; 95% confidential interval: 1.17-2.80) after adjustment for age, sex, and other confounders.…”
Section: Chronic Heart Failure and Muscle Maintenancementioning
confidence: 89%
“…Cross‐sectional analysis among 3493 non‐institutionalized older adults found that low muscle mass and low muscle function are independent risk factors for losing physical independence in later life. However, individuals with both low muscle mass and low muscle function presented the highest risk for losing physical independence . In addition, a prospective study suggested that muscle strength rather than muscle mass at baseline was associated with increased falls risk score and fracture incidence at 10 years follow‐up in community‐dwelling older adults …”
Section: Discussionmentioning
confidence: 99%